1999
DOI: 10.1097/00007890-199910270-00008
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Transplantation of Organs Procured From Bacteremic Donors1

Abstract: Organs transplanted from bacteremic donors do not transmit bacterial infection or result in poorer outcomes. Use of organs from these donors could help increase organ availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
132
3
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 15 publications
2
132
3
5
Order By: Relevance
“…4 Two recent studies comprising a large number of patients have shown that donor bacteremia did not portend a higher risk of infectious complications or compromise graft or patient survival. 1,2 The most frequent cause of the donor bacteremias in these studies was gram-positive bacteria, of which S. aureus was the predominant pathogen. A vast majority of the recipients of organs retrieved from bacteremic donors in the aforementioned studies had received antimicrobial therapy.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…4 Two recent studies comprising a large number of patients have shown that donor bacteremia did not portend a higher risk of infectious complications or compromise graft or patient survival. 1,2 The most frequent cause of the donor bacteremias in these studies was gram-positive bacteria, of which S. aureus was the predominant pathogen. A vast majority of the recipients of organs retrieved from bacteremic donors in the aforementioned studies had received antimicrobial therapy.…”
mentioning
confidence: 89%
“…In the report by Freeman et al, 91% of the recipients had received antibiotics for a mean of 3.8 days. 2 These data suggest that with appropriately administered antibiotic therapy, organs from bacteremic donors can be successfully transplanted without incurring an additional risk for infection or allograft dysfunction in the recipient.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[128][129][130][131] However, by using prophylactic antibiotics in recipients immediately after transplantation, two studies totaling 124 organ recipients have demonstrated no transmission of bacterial infection from bacteremic donors to organ recipients. 132,133 In an analysis of all organ donors cared for by the New England Organ bank between 1990 and 1996, only 95 (5.1%) of 1,775 organ donors were identified as being bacteremic. 133 No evidence of bacterial transmission could be identified in 212 recipients and there was no difference in allograft or recipient survival for recipients of organs from bacteremic as compared to non-bacteremic donors.…”
Section: Infectious Considerationsmentioning
confidence: 99%
“…132,133 In an analysis of all organ donors cared for by the New England Organ bank between 1990 and 1996, only 95 (5.1%) of 1,775 organ donors were identified as being bacteremic. 133 No evidence of bacterial transmission could be identified in 212 recipients and there was no difference in allograft or recipient survival for recipients of organs from bacteremic as compared to non-bacteremic donors.…”
Section: Infectious Considerationsmentioning
confidence: 99%